2020
DOI: 10.1021/acs.jafc.9b07632
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Bacterial Gene Cluster for Deglycosylation of Toxic Potato Steroidal Glycoalkaloids α-Chaconine and α-Solanine

Abstract: Potato juice is a byproduct of starch processing currently used as feed. However, potato proteins are an untapped source of high-protein food for human nutrition if harmful constituents notably glycoalkaloids (GAs) are detoxified. The two principle GAs found in potato are α-chaconine and α-solanine, both consisting of a solanidine aglycone with a carbohydrate side chain. The first step in the detoxification of these compounds is the removal of the trisaccharide. Whole-genome sequencing of a bacterial isolate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…Hennessy found that Arthrobacter sp. S41 could degrade α-solanine due to a novel enzyme (Hennessy et al, 2020), but in the present study, the concentration of α-solanine increased in only the B. coagulans R11-fed groups and tended to decrease in the Pb group compared with the Blank group. Thus, we concluded that B. coagulans R11 could stimulate α-solanine production rather than inhibit bacterial growth, especially in the condition of lead tolerance.…”
Section: α-Solanine Was a Major Alkaloid Metabolite In The B Coagulacontrasting
confidence: 68%
“…Hennessy found that Arthrobacter sp. S41 could degrade α-solanine due to a novel enzyme (Hennessy et al, 2020), but in the present study, the concentration of α-solanine increased in only the B. coagulans R11-fed groups and tended to decrease in the Pb group compared with the Blank group. Thus, we concluded that B. coagulans R11 could stimulate α-solanine production rather than inhibit bacterial growth, especially in the condition of lead tolerance.…”
Section: α-Solanine Was a Major Alkaloid Metabolite In The B Coagulacontrasting
confidence: 68%
“…Previously, an α- l -rhamnosidase from the actinobacteria Arthrobacter sp. S41 was reported as part of the gene cluster involved in the first step of potato glycoalkaloid detoxification . Here, five genes were related to the first steps of flavanone catabolism.…”
Section: Resultsmentioning
confidence: 99%
“…S41 was reported as part of the gene cluster involved in the first step of potato glycoalkaloid detoxification. 50 Here, five genes were related to the first steps of flavanone catabolism. Considering the cellular location of both enzymes and the substrate specificities, we propose a catabolic pathway for the hydrolysis of hesperidin and the subsequent generation of monosaccharides (Table 2).…”
Section: Table 2 Kinetic Parameters Of Recombinantmentioning
confidence: 99%
“…Furthermore, it has been shown that 5% of α-chaconine and α-solanine were hydrolyzed to other intermediate structures during a 3 h simulated in vitro digestion [25]. A recent study also discovered a bacterial gene cluster involved in deglycosylations of α-chaconine and α-solanine and thereby potentially detoxification of the potato GAs [35].…”
Section: Glycoalkaloids In Potato Protein Isolatesmentioning
confidence: 99%